Analysis of Centralized and Decentralized Education Financing Models in Indonesia - Farosa, Farosa; Sri Dewi Ayu Al Farina; Robiatul Adawiyah; Sofi, Sofi (Penerbit Presisi Pustaka, 2026)
This article analyzes the centralized and decentralized models of education financing in Indonesia. Education financing plays a crucial role in ensuring equity, quality, and sustainability of education services. The centralized model emphasizes national standardization and equal distribution through government control, while the decentralized model provides autonomy to local governments and educational institutions in managing financial resources based on contextual needs. This study employs library research by reviewing scientific articles, books, and policy documents related to education financing. The analysis shows that the centralized model ensures national standards, efficiency, and control mechanisms but lacks flexibility at the local level. Meanwhile, the decentralized model encourages community participation, responsiveness, and innovation, yet it risks widening regional disparities due to fiscal and managerial capacity differences. The study concludes that Indonesia requires a hybrid financing model that balances national equity and local autonomy. Strengthening regional capacity, transparent governance, and adaptive financial policies are essential to achieve equitable and high-quality education in Indonesia.